2020
DOI: 10.1096/fj.202000754r
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of cyclic‐GMP levels and inhibition of cGMP‐dependent protein kinase activate p21 Cip1 /p27 Kip1 pathways and lead to renal fibrosis and dysfunction

Abstract: Cell‐cycle regulatory proteins (p21Cip1/p27Kip1) inhibit cyclin and cyclin‐dependent kinase (CDK) complex that promotes fibrosis and hypertrophy. The present study examined the role of CDK blockers, p21Cip1/p27Kip1 in the progression of renal fibrosis and dysfunction using Npr1 (encoding guanylyl cyclase/natriuretic peptide receptor‐A, GC‐A/NPRA) gene‐knockout (0‐copy; Npr1−/−), 2‐copy (Npr1+/+), and 4‐copy (Npr1++/++) mice treated with GC inhibitor, A71915 and cGMP‐dependent protein kinase (cGK) inhibitor, (R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 83 publications
0
22
0
Order By: Relevance
“…These growth factors are key in survival and angiogenesis of MSCs [50,52]. But, in contrast, Oct4 deletion resulted in increased expression of proin ammatory (IL6) and pro-brotic (TGFβ1) cytokines critically involved in brosis [11]. This change is correlated with reduced MEndoT and increased brosis in MSCs under hypoxia.…”
Section: Discussionmentioning
confidence: 95%
“…These growth factors are key in survival and angiogenesis of MSCs [50,52]. But, in contrast, Oct4 deletion resulted in increased expression of proin ammatory (IL6) and pro-brotic (TGFβ1) cytokines critically involved in brosis [11]. This change is correlated with reduced MEndoT and increased brosis in MSCs under hypoxia.…”
Section: Discussionmentioning
confidence: 95%
“…These growth factors are key in survival and angiogenesis of MSCs [ 53 , 55 ]. But, in contrast, Oct4 deletion resulted in increased expression of pro-inflammatory (IL6) and pro-fibrotic (TGFβ1) cytokines critically involved in fibrosis [ 12 ]. This change is correlated with reduced MEndoT and increased fibrosis in MSCs under hypoxia.…”
Section: Discussionmentioning
confidence: 99%
“…CDKN1B (p27 Kip1) was targeted by miR-377. CDKN1B has been reported to regulate G 1 progression and maintain the cell function in response to cell proliferation inhibition or cell differentiation [36,37]. In addition, it has been confirmed that CDKN1B can act as a key modulator in cell growth by induction of CDK2 and Cyclin E1 [38,39].…”
Section: Plos Onementioning
confidence: 90%